Effect of heat resistant coating on the drilled hole quality of hybrid fiber reinforced epoxy composite - Kabir, S. (Novel Carbon Resource Sciences, 2020)
Drilling is considered an inevitable operation for joining components in automotive and aerospace industries. Hybrid fiber reinforced polymer (HFRP) composites have attained enormous attention due to their light weight and higher strength. In this study, HFRP composite was made of glass, carbon fibers and epoxy. The vacuum infusion molding technique is used to fabricate HFRP composites. Physical and mechanical properties of HFRP composites were analyzed according to ASTM standard. Heat resistant coating was made of conventional coating ingredients with fillers as a binder to enhance coating performance. This coating was applied on HFRP composite. Drilling performance was tested for HFRP and coated HFRP composites to examine the impact of coating of the composite in term of drilled hole quality. Results showed that density was reduced by 10 after applying the coating in HFRP composite. The tensile and flexural strength were found around 441.27 MPa and 409 MPa, respectively. The coating was effective in terms of improving drilled hole quality by minimizing delamination factor. It was found higher with the increment of spindle speed and feed rate for both coated and uncoated HFRP composite samples. Coated samples showed less DF at the entrance as well as exit compared to uncoated composites. Â© 2020, Novel Carbon Resource Sciences. All rights reserved.